2014
DOI: 10.1111/hel.12150
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐Utility Analysis of Endoscopic Surveillance of Patients with Gastric Premalignant Conditions

Abstract: Endoscopic surveillance every 3 years of patients with premalignant conditions is cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 68 publications
(82 reference statements)
2
52
1
8
Order By: Relevance
“…As such, there is a point in the progression of the disease when a significant risk of cancer development remains despite H pylori eradication. It is at this point that secondary prevention (eg, endoscopic surveillance) programs may become cost-effective in reducing gastric cancer deaths 15, 17, 18 . Candidates who might be suitable for non-invasive, secondary prevention surveillance programs can be identified based on serum levels of pepsinogen, which can be used to determine their risk for gastric cancer (Figure 1).…”
Section: H Pylori-associated Gastric Cancermentioning
confidence: 99%
“…As such, there is a point in the progression of the disease when a significant risk of cancer development remains despite H pylori eradication. It is at this point that secondary prevention (eg, endoscopic surveillance) programs may become cost-effective in reducing gastric cancer deaths 15, 17, 18 . Candidates who might be suitable for non-invasive, secondary prevention surveillance programs can be identified based on serum levels of pepsinogen, which can be used to determine their risk for gastric cancer (Figure 1).…”
Section: H Pylori-associated Gastric Cancermentioning
confidence: 99%
“…is cross-sectional study of patients scheduled for an upper endoscopy procedure provided utilities and selfreported QoL data for a nationwide population with a validated questionnaire in a sample of patients embracing all stages of the carcinogenic cascade for gastric adenocarcinoma. ese results, although speci c to the studied population, might be relevant to further cost-utility studies in gastric cancer as a recent systematic review showed that utilities were relevant in several studies for the nal results of the economic analysis, namely QoL in diseased patients and also a er treatments for cancer [7,8].…”
Section: Discussionmentioning
confidence: 93%
“…To the best of our knowledge this study is the first providing utilities for all stages of the gastric cancer cascade using a single health utilities measurement instrument. e study provides very useful information for authors conducting cost-utility analysis by incorporating utilities in their Markov models [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to "random" biopsies according to the updated Sydney protocol, also targeted samples from visible lesions should be taken to increase the diagnostic yield [142]. Although the strategy of 3-yearly endoscopic surveillance seems to be successful and cost effective also in a European setting, further prospective studies are required to deliver definite proof of its benefit [143][144][145]. The main issue remains the primary identification of patients who should undergo endoscopic surveillance.…”
Section: Secondary Preventionmentioning
confidence: 99%